Feasibility of using a hand-held device to characterize tendon tissue biomechanics. - Sahand Sohirad; David Wilson; Charlotte Waugh; Evan Finnamore; Alexander Scott (PLoS ONE)
Objectives To examine the feasibility of using the MyotonPRO digital palpation device in measuring the transverse stiffness of tendon tissue. Design Experimental study. Methods The MyotonPRO was used to measure the stiffness and related properties of ballistics gel in comparison with an external materials testing system (PCB electronics). The device was then used to measure the same properties of avian Achilles tendons before and after the removal of the overlying skin and subcutaneous tissue. Next, the test-retest reliability of the Achilles and patellar tendons was determined in humans. Finally, the stiffness of the Achilles tendon was measured before and after competitive running races of varying distances (10, 21 and 42 km, total number of athletes analyzed = 66). Results The MyotonPRO demonstrated a high degree of consistency when testing ballistics gel with known viscoelastic properties. The presence of skin overlying the avian Achilles tendon had a statistically significant impact on stiffness (p<0.01) although this impact was of very small absolute magnitude (with skin; 728 Nm ±17 Nm, without skin; Nm 704 Nm ±7 Nm). In healthy adults of normal body mass index (BMI), the reliability of stiffness values was excellent both for the patellar tendon (ICC, 0.96) and the Achilles tendon (ICC,0.96). In the the field study, men had stiffer tendons than women (p<0.05), and the stiffness of the Achilles tendon tended to increase following running (p = 0.052). Conclusions The MyotonPRO can reliably determine the transverse mechanical properties of tendon tissue. The measured values are influenced by the presence of overlying skin, however this does not appear to compromise the ability of the device to record physiologically and clinically relevant measurements.